Satellite Observed Land Surface Greening in Summer Controlled by the Precipitation Frequency Rather Than Its Total Over Tibetan Plateau - Ying Liu; Chaoyang Wu; Rachhpal S. Jassal; Xiaoyue Wang; Rong Shang (Earth's Future, 2022)
Abstract Land surface greening has substantially changed the carbon sequestration and hydrological processes over Tibetan Plateau (TP). Previous studies have revealed that the increased total precipitation (Ptotal) is the main driver of the enhanced peak growth in TP. However, the role of precipitation pattern, especially the frequency of precipitation (Pfreq, number of rainy days [>0.1 mm]), has not been well analyzed. We used time series of satellite‐derived Normalized Difference Vegetation Index (NDVI) to investigate the effect of Pfreq in controlling the peak growth (the maximum of the NDVI [NDVImax]) of different vegetation types in TP for the period of 1982–2015. We found that the widespread greening trend with Ptotal disappeared when Pfreq was introduced as a controlling variable, and that Pfreq alone contributed more than Ptotal to the increase of NDVImax. The underlying mechanism for the higher contribution of Pfreq than Ptotal to NDVImax is that increased Pfreq significantly improved soil moisture, reduced daytime temperature while increased nighttime temperature, thereby alleviating summer drought. Our results highlight the importance of Pfreq in interpreting the variation of peak growth, and these effects might be better represented in ecosystem models by considering Pfreq rather than Ptotal alone with future climate change.